Corrosion fatigue investigations on cast, forged and welded nickel-martensitic steels for hydro turbines. Issue 1 (1st September 2022) - Leibing, B; Von Locquenghien, F; Rückle, D; Schellenberg, G
Abstract: Facing an increased demand for flexible operation of hydro power plants (HPPs), Francis runners are substantially subjected to operating conditions beyond the traditional operating ranges. In order to ensure a reliable service of major HPP components covering their complete service life, a fundamental understanding of both load and material fatigue behavior is essential. Due to the cyclic loading in water, reliable corrosion fatigue data is required for the runner fatigue assessments. In previous publications, a state-of-the-art corrosion fatigue testing campaign within a collaborative German research project was described and results for a common cast steel used for the manufacturing of hydro runners were presented. The material testing program for the 13 % Chromium and 4 % Nickel steel has advanced since then and important aspects beyond varying water qualities and different stress ratios have been investigated. Within this conference contribution, corrosion fatigue investigations that were carried out on cast, forged and welded nickel-martensitic steels are described and recently gained results are presented.